Monocyte activation in patients with non-seminomatous germ cell tumour of the testis before and after tumour eradication. Issue 5 (May 1996) - Trulson, A; Nilsson, S; Venge, P
Abstract : AIMS: To investigate the kinetics of normalisation of monocyte oxidative activity following tumour eradication. METHODS: Whole blood lucigenin enhanced chemiluminescence was studied in patients with non-seminomatous germ cell tumours. Group 1 comprised 14 patients who had been "cured" of their cancer (the term "cured" as used in this report denotes a relapse free period of at least three years). Group 2 comprised 15 patients who were followed from diagnosis to up to two years after the start of treatment. RESULTS: Lucigenin enhanced chemiluminescence of whole blood in the "cured" patients was similar to that of controls and lower than that in patients who had not yet received chemotherapy (group 2). After treatment, chemiluminescence decreased slowly and did not normalise until 18 months after the start of treatment. Tumour necrosis factor alpha (TNF alpha) concentrations were normal in "cured" patients but were raised in those who had not yet received treatment. TNF alpha was normalised 12 months after start of treatment. Alpha-fetoprotein concentrations were raised in most patients but normalised rapidly after tumour eradication. CONCLUSIONS: The activity of blood monocytes, as measured by whole blood lucigenin enhanced chemiluminescence, is increased in cancer. This activity may be a consequence of the presence of tumour cells. Immunocompetent cells remain active for over a year after eradication of the tumour.